One of these ads is not like the other: Viewer inability to differentiate issue ads from candidate ads - Forbus, R.; Marchant-Shapiro, T.; Singh, A.S. (International Journal of Interdisciplinary Civic and Political Studies, 2024)
For more than a decade, since the US Supreme Court ruled in Citizen’s United (2010), individuals and groups interested in the outcome of elections have increasingly donated to outside groups that avoid the restrictions imposed on candidates and traditional political action committees (PACs). As a result, total election spending more than doubled in the first five years and has continued to increase since then. Although American political advocacy groups refrain from formal electioneering, much of the increase in spending since Citizen’s United has been directed toward election campaigns under the guise of issue-advocacy ads. This raises the question of whether voters perceive a difference between candidate-sponsored ads and campaign-focused issue-advocacy ads. Unexamined is the impact that advertising by outside groups has on voters and whether voters are even aware of the sponsors of the ads they view. This study addresses whether voters can differentiate between ads sponsored by candidates or outside groups. Using an experimental design, we find that viewers cannot determine the sponsor of campaign ads, despite federal requirements for sponsor disclaimers. © 2024 Common Ground Research Networks. All rights reserved.
Keywords: Ad Differentiation; Ad Sponsorship; Campaign Ads; Issue-Advocacy Ads; Political Ad Disclaimers; Voter Perceptions; dept.mrk; dept.psc; peer-reviewed